Translocal life and integration of highly-skilled migrants in Germany - Föbker, Stefanie; Imani, Daniela; Nipper, Josef; Otto, Marius; Pfaffenbach, Carmella (ERDKUNDE, 2016)
This paper addresses the living situations of highly-skilled migrants in Germany, taking managers and persons working in the arts in North Rhine-Westphalian cities as examples. With reference to integration concepts as well as approaches to transnational migration and translocality, the results of qualitative guideline-based interviews conducted with these groups are presented. The focus is on the highly-skilled migrants’ professional work conditions, their translocal mobility practices, as well as their shaping of everyday practices and networks in their German places of residence. The depicted networks and translocal practices of highly-skilled migrants reveal existing integration options and aspirations. Both, options and aspirations, are limited both by the temporality of their stays, their heavy workloads, their often limited knowledge of the German language, their focus on international networks and only little interest for social contacts on the part of the host society.